Tristate fluid as well as preparation method and application thereof
By introducing polymer thickeners, surfactants, and hydrophobic aerogel particles into the fluid, a three-phase fluid structure with continuous interpenetration of solid, liquid, and gas phases is formed, which solves the stress relaxation problem of porous fluid materials under mechanical force and realizes the application of low-density, high-performance fluid materials.
Patent Information
- Application Number
- CN202511763082.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-27
- Publication Date
- 2026-01-23
AI Technical Summary
The pore structure of existing porous fluid materials is relatively isolated, making it impossible to form a continuous and stable porous network. Furthermore, the stress relaxation dynamics under mechanical force are slow, which limits their applications in high-performance shock absorption and cushioning, breathable and heat-insulating fluids, and high-performance material molding.
A three-phase fluid structure consisting of a polymer thickener, a surfactant, and hydrophobic aerogel particles is uniformly dispersed in an aqueous phase to form a continuous interpenetrating solid-liquid-gas three-phase structure. The hydrophobic aerogel particles are then fully dispersed in an amphiphilic polymer aqueous solution through a stirring process to prepare a continuous and stable solid-gas network.
It achieves low density, air permeability, and wide compressibility of fluid materials, exhibiting excellent shear and compression dual-mode viscoelasticity and vibration damping properties, and is suitable for the molding of shock absorption damping and high-performance thermal insulation materials.
Smart Images

Figure CN121378792A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a three-state fluid, specifically to a three-state fluid and its preparation method and application, belonging to the field of nanomaterials and nanotechnology. Background Technology
[0002] Unlike rigid solid materials, fluid materials, thanks to the unique advantages of their liquid phase, can adapt to complex geometries, achieve self-healing through surface tension-driven flow, and respond in real time to external stimuli such as electric fields, magnetic forces, mechanical stress, or light. These characteristics make them an important platform for dynamic adaptation in advanced technologies, driving the rapid development of smart fluid technology. In recent years, the field of stimulus-response systems has seen several breakthroughs, including light-driven ferrofluids, superfluids with programmable compressibility, porous fluids, and shear-thickening suspensions for shock resistance. These achievements highlight the potential of fluid materials to surpass traditional solid materials in dynamic environments.
[0003] In recent years, fluid materials have been shifting from auxiliary media to advanced functional materials, a paradigm shift that is expected to spur rapid development in many fields. However, fluid materials research is still in its early stages, with gaps remaining in related theoretical design and technological development. Among various fluids, porous fluids have attracted widespread attention as a new type of material, exhibiting unique advantages in novel gas adsorption and energy absorption. However, the pore structures of porous fluids are often relatively isolated, primarily provided by porous molecules, COFs, or MOFs, resulting in extremely small pore volumes. Furthermore, the utilization of these pore structures remains very limited, significantly restricting the development of porous fluid materials.
[0004] Aerogels originated in the 1930s, accidentally invented by chemist Steven S. Kistler at the University of the Pacific in California. Commonly known as "frozen smoke," they were created by extracting water from silica gel and replacing it with a gas such as carbon dioxide. After nearly a century of development, aerogel materials have formed a vast material system, generating immense scientific research value and gradually achieving commercialization. They have important applications in aerospace, wearable devices, new energy vehicles, and transportation pipelines. Aerogels possess a typical nanoscale, continuously interpenetrating, open porous network structure, offering a natural advantage in confining air. Their pore size is smaller than the free path of air molecules, meaning air is generally "stationary" inside the aerogel. Furthermore, compared to porous molecules, COFs, and MOFs, aerogels exhibit tunable pore structures, high specific surface areas, high pore volumes, and tunable multi-scale morphologies. They are easily manipulated in solution phases for particle arrangement and assembly, making them one of the best candidates for developing novel high-performance fluid materials. Therefore, by utilizing the aerogel structure and embedding it into fluid materials, it is hoped that a lightweight, high-performance fluid material can be developed.
[0005] Most fluid materials are currently in a single phase, i.e., liquid, which often has high density and many of their physical and chemical properties are difficult to control effectively.
[0006] In recent years, although there have been reports on porous fluids, and researchers have dispersed porous particles in fluid materials to obtain porous fluids, which has attracted widespread attention, the pore structures in existing porous fluids are relatively isolated and dispersed, and cannot form a continuous and stable porous network. This still has shortcomings for applications such as high-performance shock absorption and cushioning, breathable and heat-insulating fluids, and high-performance material molding.
[0007] Furthermore, the pore structure in existing porous fluids is mostly provided by porous molecules, COF, and MOF. However, these porous materials have extremely small pore volumes, and during repeated circulation, the stress relaxation dynamics of the fluid under mechanical force are slow, which greatly limits the performance limits of porous fluid materials. Summary of the Invention
[0008] The main objective of this invention is to provide a three-state fluid and its preparation method to overcome the shortcomings of the prior art.
[0009] Another object of the present invention is to provide applications of the three-state fluid.
[0010] To achieve the aforementioned objectives, the technical solution adopted by this invention includes: This invention provides a three-state fluid comprising: an aqueous phase, a polymeric thickener, a surfactant, and hydrophobic aerogel particles. The polymeric thickener, surfactant, and hydrophobic aerogel particles are uniformly dispersed in the aqueous phase, and the hydrophobic aerogel particles form a continuous three-dimensional network in the aqueous phase. The three-state fluid has a structural characteristic of continuous interpenetration of solid-liquid-gas three-phase states.
[0011] This invention also provides a method for preparing a three-state fluid, comprising: Mix the polymer thickener with water to form a polymer aqueous solution; The aqueous polymer dispersion is mixed with a surfactant to form an amphiphilic polymer aqueous solution; The hydrophobic aerogel particles are fully dispersed in the amphiphilic polymer aqueous solution to obtain the three-state fluid.
[0012] This invention also provides the application of the three-state fluid in the fields of shock absorption, heat insulation material molding, or irregular aerogel composite material molding and processing.
[0013] Compared with the prior art, the beneficial effects of the present invention include at least the following: 1) The three-phase fluid material provided by this invention has the structural feature of continuous interpenetration of solid-liquid-gas three phases, taking into account the low density and ultra-lightweight properties of aerogel and the fluidity of fluid materials. It solves the problem of uniform dispersion of ultra-lightweight aerogel materials in high-density fluids, and manipulates aerogel particles to form a dynamically stable continuous solid-gas network in the fluid. It exhibits excellent performance in shock absorption and damping, high-performance thermal insulation material molding, etc., and provides a new idea for the preparation of novel fluid materials. 2) Compared with existing porous fluids and their preparation processes, the three-state fluid material of the present invention has richer performance control capabilities and the preparation method is more maneuverable. It can endow the fluid material with a continuous solid-liquid-gas interpenetrating network structure, realize the fluid's air permeability, low density and wide range compressibility, and provide advantages for the molding of high-performance and irregularly shaped materials. Attached Figure Description
[0014] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0015] Figure 1 This is a three-dimensional confocal image of the three-state fluid prepared in Example 5 of the present invention; Figure 2 This is a schematic diagram showing the continuity of the solid-gas dual-state fluid in the liquid phase of the three-state fluid prepared in Example 5 of the present invention. Figure 3A This is a schematic diagram of the shear bimodal viscoelasticity of the three-state fluid prepared in Example 5 of the present invention; Figure 3B This is a schematic diagram of the compressible bimodal viscoelasticity of the three-state fluid prepared in Example 5 of the present invention; Figure 4A The image shows the test results of the vibration acceleration of the base when industrial shock-absorbing rubber blocks are used as shock-absorbing pads. Figure 4B The vibration acceleration test results of the base were obtained by using the three-state fluid prepared in Example 5 of the present invention as a shock-absorbing pad; Figure 5 The images show physical photos of the three-state fluid and polyurethane emulsion mixed and sprayed, scraped and molded respectively to form the coating (left), film (middle) and bulk (right) irregular aerogel composite materials in Example 6 of the present invention. Detailed Implementation
[0016] In view of the current booming development of fluid materials and the unique advantages of aerogel materials, the inventors of this case have developed a three-state fluid material with a solid-liquid-gas three-phase continuous interpenetration structure, which takes into account the low density and ultra-lightweight properties of aerogel and the fluidity of fluid materials, and solves the problem of uniform dispersion of ultra-lightweight aerogel materials in high-density fluids.
[0017] The following will further explain the technical solution, its implementation process, and its principles. However, it should be understood that within the scope of this invention, the above-mentioned technical features of this invention and the technical features specifically described below (in embodiments) can be combined with each other to form new or preferred technical solutions. Due to space limitations, they will not be described in detail here.
[0018] As one aspect of the technical solution of the present invention, the three-state fluid involved includes: an aqueous phase, a polymeric thickener, a surfactant, and hydrophobic aerogel particles. The polymeric thickener, surfactant, and hydrophobic aerogel particles are uniformly dispersed in the aqueous phase. The hydrophobic aerogel particles form a continuous three-dimensional network in the aqueous phase. The three-state fluid has a structural characteristic of continuous interpenetration of solid-liquid-gas three-phase states.
[0019] In some embodiments, the content of the polymeric thickener in the three-state fluid is 0.01~10 wt%, the content of the surfactant is 0.01~10 wt%, the content of the hydrophobic aerogel particles is 1~20 wt%, and the content of the aqueous phase is 60~95 wt%.
[0020] In some embodiments, the aqueous phase includes water, preferably deionized water, but is not limited thereto.
[0021] In some embodiments, the pore structure of the hydrophobic aerogel particles consists of macropores with a pore size greater than 50 nm, mesopores with a pore size of 2 nm to 50 nm, and micropores with a pore size less than 2 nm.
[0022] In some embodiments, the particle size of the hydrophobic aerogel particles is, for example, a diameter of 10 μm to 1000 μm.
[0023] In some embodiments, the volume fraction of the hydrophobic aerogel particles in the three-state fluid is 35% to 95%.
[0024] In some embodiments, the hydrophobic aerogel particles comprise silica aerogels modified with hydrophobic materials, wherein the hydrophobic materials include, but are not limited to, one or more of the following: trimethylchlorosilane, dimethyldichlorosilane, methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane, hexamethyldisilazane, polydimethylsiloxane, etc.
[0025] In some embodiments, the polymeric thickener includes, but is not limited to, one or more of xanthan gum, gellan gum, veland gum, carrageenan, guar gum, agar, hyaluronic acid, hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, methyl cellulose, polyacrylic acid, polyacrylamide, hydrophobically modified hydroxyethyl cellulose, hydrophobically modified ethylene oxide polyurethane, xanthodextrin, etc.
[0026] In some preferred embodiments, the polymeric thickener is one or more of xanthan gum, gellan gum, veland gum, carrageenan, guar gum, agar, hyaluronic acid, hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, methyl cellulose, hydrophobically modified ethylene oxide polyurethane, hydrophobically modified alkali-swellable polymeric emulsion, etc.
[0027] In some embodiments, the surfactant includes, but is not limited to, one or more of the following: sodium stearate, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, benzalkonium chloride, benzalkonium bromide, hexadecyltrimethylammonium bromide, cocamidopropyl betaine, sodium lauroyl sarcosinate, fatty acid sorbitan, polysorbate, lecithin, polyoxyethylene ether, alkyl glucoside, fatty acid glycerides, etc.
[0028] In some more preferred embodiments, the surfactant is one or more of sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, fatty acid sorbitan, polysorbate, lecithin, etc.
[0029] In some implementations, the compressible volumetric strain of the three-state fluid is 1% to 60%.
[0030] In some embodiments, the density of the three-state fluid is 0.2 g / cm³. 3 ~0.95 g / cm 3 .
[0031] In summary, the three-state fluid of the present invention has the structural feature of continuous interpenetration of solid-liquid-gas three-phase states, takes into account the low density characteristics of aerogel and the fluidity characteristics of fluid materials, and manipulates aerogel particles to form a dynamically stable continuous solid-gas network in the fluid, exhibiting excellent shear and compression dual-mode viscoelasticity, vibration damping and material forming ability, and showing excellent performance in vibration damping, high-performance thermal insulation material forming and other aspects.
[0032] As another aspect of the technical solution of the present invention, it also relates to a method for preparing the three-state fluid, comprising: Mix the polymer thickener with water to form a polymer aqueous solution; The aqueous polymer dispersion is mixed with a surfactant to form an amphiphilic polymer aqueous solution; The hydrophobic aerogel particles are fully dispersed in the amphiphilic polymer aqueous solution to obtain the three-state fluid.
[0033] In some preferred embodiments, the preparation method specifically includes: mixing a polymeric thickener with water and stirring at a speed of 500 rpm to 2000 rpm for 10 min to 120 min to obtain a uniform polymeric aqueous solution.
[0034] In some preferred embodiments, the mass fraction of the polymer thickener in the polymer aqueous solution is 0.01% to 10%; if its content is too low, the yield stress of the liquid phase will be low and insufficient to stabilize the aerogel particles, and if its content is too high, the liquid phase will have poor fluidity. Therefore, its concentration is preferably 0.1% to 5%.
[0035] In some preferred embodiments, the preparation method specifically includes: adding a surfactant to the polymer aqueous solution and mechanically stirring at room temperature for 10 min to 120 min to obtain a uniform amphiphilic polymer aqueous solution.
[0036] In some preferred embodiments, the surfactant accounts for 0.01% to 10% of the total mass of the polymer aqueous solution; if its content is too low, it is insufficient to disperse the hydrophobic aerogel particles, and if its content is too high, it will cause the liquid to actively invade the hydrophobic pores of the aerogel and fail to form a stable gas-liquid-solid three-phase structure. Therefore, its concentration is preferably 0.1% to 3%.
[0037] In some preferred embodiments, the preparation method specifically includes: mixing hydrophobic aerogel particles with an amphiphilic polymer aqueous solution, stirring at a speed of 1000 rpm to 25000 rpm for 2 to 30 seconds, repeating this operation 1 to 5 times to obtain a three-state fluid.
[0038] In some preferred embodiments, the hydrophobic aerogel particles account for 1% to 20% of the total mass of the amphiphilic polymer aqueous solution. If the content is too high, it will lead to poor fluidity of the fluid material and affect the molding process. Therefore, the concentration is preferably 1% to 15%.
[0039] The main concept behind the preparation method of this invention is as follows: First, a polymeric aqueous dispersion with a specific yield stress is designed and prepared. Then, a surfactant is introduced into the aqueous dispersion to impart good amphiphilic properties, which helps disperse aerogel particles. Finally, during stirring, hydrophobic aerogel particles are introduced into the above aqueous dispersion to obtain a three-state fluid.
[0040] In some more specific implementation schemes, a method for preparing a three-state fluid includes the following steps: 1) Preparation of polymeric aqueous solution: Weigh a certain amount of polymeric thickener, mix it with deionized water, and stir rapidly for 30-120 minutes to obtain a uniform, viscous polymeric aqueous solution. The mass fraction of the polymeric thickener in the polymeric aqueous solution is 0.01%-10%, preferably 0.1%-5% by mass. 2) Adding a surfactant: Add a surfactant to the above-mentioned polymer aqueous solution and mechanically stir at room temperature to ensure thorough mixing, thereby obtaining a homogeneous amphiphilic polymer aqueous solution. The surfactant accounts for 0.01% to 10% of the total mass of the polymer aqueous solution, preferably 0.1% to 3% by mass. 3) Dispersing hydrophobic silica aerogel particles: Mix the hydrophobic silica aerogel particles with the above-mentioned amphiphilic polymer aqueous solution in a Weinlin stirrer. To prevent water from penetrating the particle structure, stir at a high speed of 1000 rpm to 25000 rpm for 2 to 30 seconds each time, repeating this operation 1 to 5 times to ensure that the hydrophobic silica aerogel particles are fully dispersed in the solution, forming a three-state fluid. The amount of hydrophobic silica aerogel particles is 1% to 20% of the total mass of the amphiphilic polymer aqueous solution, preferably 1% to 15%.
[0041] In summary, compared with existing porous fluids and their preparation processes, the preparation method of the present invention has richer performance control capabilities, and the related technical solutions are more maneuverable. It can endow fluid materials with a continuous solid-liquid-gas interpenetrating network structure, realize the fluid's permeability, low density and wide range compressibility, and provide advantages for the molding of high-performance and irregularly shaped materials.
[0042] As another aspect of the technical solution of the present invention, it also relates to the application of the three-state fluid.
[0043] Specifically, it can be used in fields such as shock absorption, molding and processing of irregularly shaped aerogel composite materials.
[0044] Furthermore, applications in the field of vibration damping include: encapsulating the tri-state fluid in a non-elastic, high-strength bag, which can be placed directly under various types of mechanical equipment to isolate vibrations between the machinery and the ground. Alternatively, the tri-state fluid can be encapsulated in a cylinder with a piston to create a vibration damping platform, reducing the damage to ground structures caused by mechanical vibrations.
[0045] Further, the application includes: mixing the three-state fluid with an aqueous resin emulsion, followed by film formation to obtain an aerogel composite coating, aerogel composite film, or aerogel composite block. The aqueous resin emulsion includes at least one of acrylic resin emulsion, polyurethane emulsion, epoxy resin emulsion, etc., but is not limited to these. The film formation method includes at least one of spraying, blade coating, injection molding, etc., but is not limited to these.
[0046] Furthermore, the specific applications include: mixing the three-state fluid with an aqueous resin emulsion (acrylic resin emulsion, polyurethane emulsion, epoxy resin emulsion, etc.) to prepare a liquid fluid material that can be prepared into low-density, low-thermal-conductivity aerogel composite coatings, aerogel composite films, aerogel composite blocks, etc. by spraying, scraping, injection molding, etc., and then drying under normal pressure.
[0047] To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. It should be noted that the following embodiments are intended to facilitate understanding of this invention and are not intended to limit it in any way. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or according to the conditions recommended by the manufacturer.
[0048] Example 1 1) Preparation of polymer aqueous solution: Weigh 0.1 g xanthan gum and mix it with 99.9 g deionized water. Stir rapidly at 1200 rpm for 30 minutes to obtain a homogeneous xanthan gum solution. 2) Adding surfactant: Add 0.2 g of polysorbate surfactant (Tween 80) to the above xanthan gum solution, and mechanically stir at room temperature for 30 min to mix it thoroughly to obtain Tween 80 / xanthan gum aqueous solution; 3) Dispersing hydrophobic silica aerogel particles: 1.5 g of methyl-type hydrophobic silica aerogel particles (trimethylchlorosilane-modified silica aerogel, particle size 30 μm, density 0.05 g / cm³) were dispersed. 3 Mix the above-mentioned Tween 80 / xanthan gum aqueous solution with 70 mL in a Weinlin stirrer. To prevent moisture from penetrating the particle structure, stir at a high speed of 20,000 rpm for 2 seconds each time, repeating this operation 5 times to ensure that the hydrophobic silica aerogel particles are fully dispersed in the solution, forming a three-state fluid.
[0049] Example 2 1) Preparation of polymer aqueous solution: Weigh 0.2 g xanthan gum and mix it with 99.8 g deionized water. Stir rapidly at 1200 rpm for 30 minutes to obtain a homogeneous xanthan gum solution. 2) Adding surfactant: Add 0.3 g of polysorbate surfactant (Tween 80) to the above xanthan gum solution, and mechanically stir for 30 min at room temperature to mix it thoroughly, so as to obtain Tween 80 / xanthan gum aqueous solution; 3) Dispersing hydrophobic silica aerogel particles: 1.5 g of methyl-type hydrophobic silica aerogel particles (dimethyldichlorosilane-modified silica aerogel, particle size 10 μm, density 0.05 g / cm³) were dispersed. 3 Mix the above-mentioned Tween 80 / xanthan gum aqueous solution with 70 mL in a Weinlin stirrer. To prevent moisture from penetrating the particle structure, stir at a high speed of 20,000 rpm for 2 seconds each time, repeating this operation 5 times to ensure that the hydrophobic silica aerogel particles are fully dispersed in the solution, forming a three-state fluid.
[0050] Example 3 1) Preparation of polymer aqueous solution: Weigh 0.4 g xanthan gum and mix it with 99.6 g deionized water. Stir rapidly at 1000 rpm for 30 minutes to obtain a homogeneous xanthan gum solution. 2) Adding surfactant: Add 0.3 g of polysorbate surfactant (Tween 80) to the above xanthan gum solution, and mechanically stir at room temperature for 30 min to mix it thoroughly to obtain Tween 80 / xanthan gum aqueous solution; 3) Dispersion of hydrophobic silica aerogel particles: 1.5 g of methyl-type hydrophobic silica aerogel particles (methyltrimethoxysilane-modified silica aerogel, particle size 5000 μm, density 0.05 g / cm³) were dispersed. 3 Mix the above-mentioned Tween 80 / xanthan gum aqueous solution with 70 mL in a Weinlin stirrer. To prevent moisture from penetrating the particle structure, stir at a high speed of 20,000 rpm for 2 seconds each time, repeating this operation 5 times to ensure that the hydrophobic silica aerogel particles are fully dispersed in the solution, forming a three-state fluid.
[0051] Example 4 1) Preparation of polymer aqueous solution: Weigh 0.4 g xanthan gum and mix it with 99.6 g deionized water. Stir rapidly at 1500 rpm for 30 minutes to obtain a homogeneous xanthan gum solution. 2) Adding surfactant: Add 0.3 g of polysorbate surfactant (Tween 80) to the above xanthan gum solution, and mechanically stir at room temperature for 30 min to mix it thoroughly to obtain Tween 80 / xanthan gum aqueous solution; 3) Dispersion of hydrophobic silica aerogel particles: 2.0 g of methyl-type hydrophobic silica aerogel particles (dimethyldimethoxysilane-modified silica aerogel, particle size 1000 μm, density 0.05 g / cm³) were dispersed. 3 Mix the above-mentioned Tween 80 / xanthan gum aqueous solution with 60 mL in a Weinlin stirrer. To prevent moisture from penetrating the particle structure, stir at a high speed of 20,000 rpm for 2 seconds each time, repeating this operation 5 times to ensure that the hydrophobic silica aerogel particles are fully dispersed in the solution, forming a three-state fluid.
[0052] Example 5 1) Preparation of polymer aqueous solution: Weigh 0.4 g xanthan gum and mix it with 99.6 g deionized water. Stir rapidly at 1200 rpm for 30 minutes to obtain a homogeneous xanthan gum solution. 2) Adding surfactant: Add 0.3 g of polysorbate surfactant (Tween 80) to the above xanthan gum solution and mechanically stir for 30 min at room temperature to obtain Tween 80 / xanthan gum aqueous solution; 3) Dispersion of hydrophobic silica aerogel particles: 2.5 g of methyl-type hydrophobic silica aerogel particles (trimethylmethoxysilane-modified silica aerogel, particle size 30 μm, density 0.05 g / cm³) were dispersed. 3 The above-mentioned Tween 80 / xanthan gum aqueous solution (50 mL) was mixed with a Weinlin stirrer. To prevent water from penetrating the particle structure, the mixture was stirred at 20,000 rpm for 2 seconds each time, and this operation was repeated 5 times to ensure that the hydrophobic silica aerogel particles were fully dispersed in the solution, forming a three-state fluid. Observation using a three-dimensional confocal microscope revealed that a large number of hydrophobic silica aerogel particles were distributed on the fluid surface, overlapping each other to form a solid network (such as...). Figure 1 As shown in the diagram, this solid network facilitates the diffusion of dyed n-hexane in the aqueous phase. Figure 2 This demonstrates the continuity of the solid-gas dual state in the liquid phase of the three-state fluid. It can be seen that hexane, which is immiscible with water, diffuses into the aqueous phase system of the three-state fluid through the aerogel solid-gas dual network when left at rest.
[0053] Figure 3A and Figure 3B The figures shown are schematic diagrams illustrating the shear and compression bimodal viscoelasticity of the three-state fluid obtained in Example 5. It can be seen that the three-state fluid (CL5) exhibits both shear and compression bimodal viscoelasticity. Figure 3A In the process, as the shear strain increases, the three-state fluid changes from a solid-like state (storage modulus G′ is greater than loss modulus G′′) to a liquid-like state (storage modulus G′ is less than loss modulus G′′), and the fluid exhibits shear viscoelasticity; Figure 3B In this study, the three-state fluid exhibits excellent low-pressure response behavior, with the hysteresis loop surface possessing energy dissipation capabilities and compressive viscoelasticity. Furthermore, after 40 cycles of compression, the hysteresis curve almost perfectly matches that of the first compression cycle, indicating good compressive stability.
[0054] This three-state fluid, encapsulated in a non-elastic, high-strength bag, can be placed directly under a vacuum pump to isolate mechanical vibrations from the ground, exhibiting better shock absorption than industrial rubber damping pads. Figure 4A and Figure 4B As shown, this is industrial rubber ( Figure 4A) and three-state fluid package ( Figure 4B Comparison of vibration damping performance devices and their effects. Figure 4A and Figure 4B In the experiment, a vacuum pump was used as the vibration source, and industrial damping rubber blocks and the three-state fluid damping pack prepared in Example 5 were used as damping pads to measure the vibration acceleration of the base. Figure 4A After the rubber block damping was applied, the vibration acceleration of the base reached 0.25g (g is the acceleration due to gravity), while Figure 4B The maximum acceleration of the base vibration after damping by the three-state fluid damping package is less than 0.1g, demonstrating excellent damping capability.
[0055] Example 6 1) Preparation of polymer aqueous solution: Weigh 0.4 g xanthan gum and mix it with 99.6 g deionized water. Stir rapidly at 1000 rpm for 30 minutes to obtain a homogeneous xanthan gum solution. 2) Adding surfactant: Add 0.3 g of polysorbate surfactant (Tween 80) to the above xanthan gum solution, and mechanically stir at room temperature for 30 min to mix it thoroughly to obtain Tween 80 / xanthan gum aqueous solution; 3) Dispersion of hydrophobic silica aerogel particles: 3.0 g of methyl-type hydrophobic silica aerogel particles (methyltriethoxysilane-modified silica aerogel, particle size 50 μm, density 0.05 g / cm³) were dispersed. 3 Mix the above-mentioned Tween 80 / xanthan gum aqueous solution with 40 mL in a Weinlin stirrer. To prevent moisture from penetrating the particle structure, stir at a high speed of 20,000 rpm for 2 seconds each time, repeating this operation 5 times to ensure that the hydrophobic silica aerogel particles are fully dispersed in the solution, forming a three-state fluid.
[0056] like Figure 5 As shown, 80% by mass of the three-state fluid obtained in Example 6 was mixed with 20% polyurethane emulsion to prepare the liquid fluid material. The resulting liquid fluid material was then coated by spraying, scraping, and injection molding, followed by atmospheric pressure drying to prepare an aerogel composite coating. Figure 5 Left), aerogel composite membrane ( Figure 5 (middle), aerogel composite block ( Figure 5 (Right) Irregularly shaped aerogel composite materials, the prepared composite aerogel material has a thermal conductivity as low as 0.028 W / (m·K) and a density of only 0.2 g / cm³. 3 It is expected to be used as a lightweight thermal insulation material.
[0057] Example 7 1) Preparation of polymer aqueous solution: Weigh 0.8 g of guar gum and mix it with 99.2 g of deionized water. Stir rapidly at 2000 rpm for 10 minutes to obtain a homogeneous guar gum solution. 2) Adding surfactant: Add 0.3 g of polysorbate surfactant (Tween 80) to the above guar gum solution, and mechanically stir at room temperature for 30 min to mix it thoroughly to obtain Tween 80 / guar gum aqueous solution; 3) Dispersion of hydrophobic silica aerogel particles: 2.5 g of methyl-type hydrophobic silica aerogel particles (dimethyldiethoxysilane-modified silica aerogel, particle size 50 μm, density 0.05 g / cm³) were dispersed. 3 Mix the above-mentioned Tween 80 / guar gum aqueous solution with 50 mL in a Weinlin stirrer. To prevent moisture from penetrating the particle structure, stir at a high speed of 20,000 rpm for 2 seconds each time, repeating this operation 5 times to ensure that the hydrophobic silica aerogel particles are fully dispersed in the solution, forming a three-state fluid.
[0058] Example 8 1) Preparation of polymer aqueous solution: Weigh 0.8 g of hydroxyethyl cellulose and mix it with 99.2 g of deionized water. Stir rapidly at 500 rpm for 120 minutes to obtain a homogeneous hydroxyethyl cellulose solution. 2) Adding surfactant: Add 0.3 g sodium dodecylbenzenesulfonate to the above hydroxyethyl cellulose solution and mechanically stir at room temperature for 30 min to mix it thoroughly, so as to obtain sodium dodecylbenzenesulfonate / hydroxyethyl cellulose aqueous solution; 3) Dispersion of hydrophobic silica aerogel particles: 2.5 g of methyl-type hydrophobic silica aerogel particles (trimethylethoxysilane-modified silica aerogel, particle size 30 μm, density 0.05 g / cm³) were dispersed. 3 The sodium dodecylbenzenesulfonate / hydroxyethyl cellulose aqueous solution was mixed with 50 mL of the above solution in a Weinlin stirrer. To prevent moisture from penetrating the particle structure, the mixture was stirred at 20,000 rpm for 2 seconds each time, and this operation was repeated 5 times to ensure that the hydrophobic silica aerogel particles were fully dispersed in the solution, forming a three-state fluid.
[0059] Example 9 1) Preparation of polymer aqueous solution: Weigh 0.01 g of methylcellulose and mix it with 99.9 g of deionized water. Stir rapidly at 800 rpm for 100 minutes to obtain a homogeneous methylcellulose solution. 2) Adding surfactant: Add 0.01 g sodium dodecyl sulfate to the above methylcellulose solution and mechanically stir for 10 min at room temperature to mix it thoroughly, so as to obtain sodium dodecyl sulfate / methylcellulose aqueous solution; 3) Dispersing hydrophobic silica aerogel particles: Methyl hydrophobic silica aerogel particles (trimethylethoxysilane-modified silica aerogel, particle size 30 μm, density 0.05 g / cm³) were dispersed. 3The sodium dodecyl sulfate / methylcellulose aqueous solution was mixed with the above-mentioned sodium dodecyl sulfate / methylcellulose aqueous solution in a Weinlin stirrer, with the methyl hydrophobic silica aerogel particles accounting for 1% of the total mass of the sodium dodecyl sulfate / methylcellulose aqueous solution. To prevent water from penetrating the particle structure, the mixture was stirred at a high speed of 25,000 rpm for 2 seconds each time, and this operation was repeated 3 times to ensure that the hydrophobic silica aerogel particles were fully dispersed in the solution, forming a three-state fluid.
[0060] Example 10 1) Preparation of polymer aqueous solution: Weigh 10 g of carboxymethyl cellulose and mix it with 90 g of deionized water. Stir rapidly at 1500 rpm for 20 minutes to obtain a homogeneous carboxymethyl cellulose solution. 2) Adding surfactant: Add 10 g of fatty acid sorbitan to the above methylcellulose solution and mechanically stir at room temperature for 120 min to mix it thoroughly, so as to obtain fatty acid sorbitan / carboxymethylcellulose aqueous solution; 3) Dispersing hydrophobic silica aerogel particles: Methyl hydrophobic silica aerogel particles (trimethylethoxysilane-modified silica aerogel, particle size 30 μm, density 0.05 g / cm³) were dispersed. 3 The methyl hydrophobic silica aerogel particles were mixed with the above-mentioned fatty acid sorbitan / carboxymethyl cellulose aqueous solution in a Weinlin stirrer, with the methyl hydrophobic silica aerogel particles accounting for 20% of the total mass of the fatty acid sorbitan / carboxymethyl cellulose aqueous solution. To prevent water from penetrating the particle structure, the mixture was stirred at a high speed of 1000 rpm for 30 seconds each time, and this operation was repeated twice to ensure that the hydrophobic silica aerogel particles were fully dispersed in the solution, forming a three-state fluid.
[0061] Comparative Example 1 The difference between this comparative example and Example 5 is that the amount of xanthan gum, a polymeric thickener, was 0.05 g. The system separated into layers within 10 min. Insufficient thickener resulted in instability of the three-state fluid and rapid phase separation.
[0062] Comparative Example 2 The difference between this comparative example and Example 5 is that the amount of surfactant Tween 80 used is 0.05 g. The resulting mixture is a semi-solid mixture with poor flowability and discontinuity. Too low a surfactant amount is not conducive to forming a "water-encapsulated hydrophobic aerogel particle" state and cannot form a uniform three-state fluid.
[0063] Comparative Example 3 The difference between this comparative example and Example 5 is that the amount of methyl-type hydrophobic silica aerogel particles used is 18 g. The resulting system is a solid powder mixture. If the amount of hydrophobic aerogel is too large, the mixture exists as a fluid encapsulated by the hydrophobic aerogel particles, failing to form a uniform and continuous three-state fluid.
[0064] Comparative Example 4 The difference between this comparative example and Example 1 is that the high molecular weight thickener xanthan gum was not added. After stirring at 20,000 rpm, the fluid material separated into layers within 2 minutes, with aerogel particles on top and an aqueous solution on the bottom, failing to obtain a homogeneous fluid material.
[0065] Comparative Example 5 The difference between this comparative example and Example 1 is that the surfactant Tween 80 was not added. After stirring at 20,000 rpm, this system only yielded two phases: an upper layer of aerogel particles and a lower layer of aqueous solution, failing to produce a homogeneous fluid material.
[0066] Comparative Example 6 The difference between this comparative example and Example 1 is that hydrophobic aerogel particles were not added. The final result was a relatively viscous, semi-transparent aqueous solution with a lower thermal conductivity than pure water and almost no compressibility.
[0067] Table 1 Performance parameters of the three-state fluids obtained in Examples 1-8 and Comparative Example 6
[0068] In Table 1, the density of all embodiments is less than that of water, indicating that the addition of hydrophobic aerogel particles introduces a certain component of air. From Embodiment 3 to Embodiment 6, as the content of hydrophobic aerogel particles increases, the density of the three-state fluid decreases, and the gas phase content in the fluid increases.
[0069] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A three-state fluid, characterized in that, include: The fluid comprises an aqueous phase, a polymeric thickener, a surfactant, and hydrophobic aerogel particles, wherein the polymeric thickener, surfactant, and hydrophobic aerogel particles are uniformly dispersed in the aqueous phase, and the hydrophobic aerogel particles form a continuous three-dimensional network in the aqueous phase. The three-phase fluid has a structural characteristic of continuous interpenetration between solid, liquid, and gas phases.
2. The three-state fluid according to claim 1, characterized in that... include: 60~95 wt% aqueous phase, 0.01~10 wt% polymeric thickener, 0.01~10 wt% surfactant and 1~20 wt% hydrophobic aerogel particles; And / or, the aqueous phase includes water; And / or, the pore structure of the hydrophobic aerogel particles consists of macropores with a pore size greater than 50 nm, mesopores with a pore size of 2 nm to 50 nm, and micropores with a pore size less than 2 nm. And / or, the diameter of the hydrophobic aerogel particles is 10 μm to 1000 μm; And / or, the volume fraction of the hydrophobic aerogel particles in the three-state fluid is 35%~95%.
3. The three-state fluid according to claim 1, characterized in that: The hydrophobic aerogel particles comprise silica aerogels modified with hydrophobic substances, wherein the hydrophobic substances include one or more combinations of trimethylchlorosilane, dimethyldichlorosilane, methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, trimethylethoxysilane, hexamethyldisilazane, and polydimethylsiloxane. And / or, the polymeric thickener comprises one or more combinations of xanthan gum, gellan gum, veland gum, carrageenan, guar gum, agar, hyaluronic acid, hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, methyl cellulose, polyacrylic acid, polyacrylamide, hydrophobically modified hydroxyethyl cellulose, hydrophobically modified ethylene oxide polyurethane, and hydrophobically modified alkali-swellable polymeric emulsion; preferably, the polymeric thickener comprises one or more combinations of xanthan gum, gellan gum, veland gum, carrageenan, guar gum, agar, hyaluronic acid, hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, methyl cellulose, hydrophobically modified ethylene oxide polyurethane, and xanthodextrin; And / or, the surfactant comprises one or more of the following: sodium stearate, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, benzalkonium chloride, benzalkonium bromide, hexadecyltrimethylammonium bromide, cocamidopropyl betaine, sodium lauroyl sarcosinate, fatty acid sorbitan, polysorbate, lecithin, polyoxyethylene ether, alkyl glucoside, and fatty acid glycerides. Preferably, the surfactant comprises one or more of the following: sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, fatty acid sorbitan, polysorbate, and lecithin.
4. The three-state fluid according to claim 1, characterized in that: The compressible volumetric strain of the three-state fluid is 1%~60%, and the thermal conductivity is 0.05~0.59 W / (m·K); And / or, the density of the three-state fluid is 0.2 g / cm³. 3 ~0.95 g / cm 3 .
5. The method for preparing a three-state fluid as described in any one of claims 1-4, characterized in that, include: Mix the polymer thickener with water to form a polymer aqueous solution; The aqueous polymer dispersion is mixed with a surfactant to form an amphiphilic polymer aqueous solution; The hydrophobic aerogel particles are fully dispersed in the amphiphilic polymer aqueous solution to obtain the three-state fluid.
6. The preparation method according to claim 5, characterized in that, include: Mix the polymer thickener with water and stir at a speed of 500 rpm to 2000 rpm for 10 min to 120 min to obtain a homogeneous polymer aqueous solution. And / or, the mass fraction of the polymer thickener in the polymer aqueous solution is 0.01% to 10%, preferably 0.1% to 5%.
7. The preparation method according to claim 5, characterized in that, include: A surfactant was added to the polymer aqueous solution, and the mixture was mechanically stirred at room temperature for 10 min to 120 min to obtain a homogeneous amphiphilic polymer aqueous solution. And / or, the surfactant accounts for 0.01% to 10% of the total mass of the polymer aqueous solution, preferably 0.1% to 3%.
8. The preparation method according to claim 5, characterized in that, include: Hydrophobic aerogel particles were mixed with an amphiphilic polymer aqueous solution and stirred at 1000 rpm to 25000 rpm for 2 to 30 seconds. This operation was repeated 1 to 5 times to obtain a three-state fluid. And / or, the mass of the hydrophobic aerogel particles accounts for 1% to 20% of the total mass of the amphiphilic polymer aqueous solution, preferably 1% to 15%.
9. The application of the three-state fluid according to any one of claims 1-4 in the field of molding and processing of shock-absorbing or irregularly shaped aerogel composite thermal insulation materials.
10. The application according to claim 9, characterized in that: The applications include: encapsulating the three-state fluid in an inelastic, high-strength bag, or encapsulating it in a cylinder with a piston; Alternatively, the application includes: mixing the three-state fluid with an aqueous resin emulsion, and then forming a film to obtain an aerogel composite coating, aerogel composite film, or aerogel composite block. Preferably, the aqueous resin emulsion includes at least one of acrylic resin emulsion, polyurethane emulsion, and epoxy resin emulsion; Preferably, the film-forming method includes at least one of spraying, scraping, and injection molding.
Citation Information
Cited By
A tri-state fluid based on hydrophobic carbon aerogel, its preparation method and application
CN122212557A